Sustaining pastoral work and welfare in Zimbabwe: Case study of pastors in Masvingo urban - Kimion Tagwirei (Verbum et Ecclesia, 2022)
A growing number of pastors in Zimbabwe are adversely affected by the economic crisis that has been caused by the lockdown measures imposed by the government to tackle the coronavirus disease 2019 (COVID-19) pandemic. Only some pastors who are financially supported by their churches and donors and others who have adopted tent-making ministry are getting through this difficult situation. There is very little study on the subject of economic sustainability of Zimbabwean pastors. The majority of the available literature is limited to a few denominations. This article applies ‘theonomic reciprocity’ theory, which integrates divine action and human participation for ecclesiastic sustainability. In this respect, tent-making was reviewed. In the context of economic volatility, this study examined the economic sustainability gap that needs to be bridged between pastoral ministry and welfare. The article discusses sustainability of congregational support for pastors and tent-making ministry in the Zimbabwean economic context. Very few pastors in Masvingo have embraced self-sustaining initiatives. Most of them are yet to integrate faith and business due to fear of diverting their attention from ministry. The study recommends pastors to consider contextually needful tent-making towards sustaining their work and welfare.